PlantMP: a database for moonlighting plant proteins. (25th April 2019) - Su, Bo; Qian, Zhuang; Li, Tianshu; Zhou, Yuwei; Wong, Aloysius
Abstract: Moonlighting proteins are single polypeptide chains capable of executing two or more distinct biochemical and/or biological functions. Here, we describe the development of PlantMP, which is a manually curated online-based database of plant proteins that are known to `moonlight'. The database contains searchable UniProt IDs and names, canonical and moonlighting functions, gene ontology numbers, plant species as well as links to the PubMed indexed articles. Proteins homologous to experimentally confirmed moonlighting proteins from the model plant Arabidopsis thaliana are provided as a separate list of `likely moonlighters'. Additionally, we also provide a list of predicted Arabidopsis moonlighting proteins reported in the literature. Currently, PlantMP contains 110 plant moonlighting proteins, 10 `likely moonlighters' and 27 `predicted moonlighters'. Organizing plant moonlighting proteins in one platform enables researchers to conveniently harvest plant-specific raw and processed data such as the molecular functions, biological roles and structural features essential for hypothesis formulation in basic research and for biotechnological innovations.